SUPPORTING E-COMMERCE AS A MARKETING COMPANY - Diyah Ruri Irawati (JAKSTIK Journal, 2004)
Electronic Commerce (e-Commerce) is very supportive in promoting, developing a company.With e-commerce will be able to provide a feasibility for the management of processingresources used. Among these resources, e-commerce is in the process of marketingmanagement support to achieve goals. It dikarena e-commerce can change the type ofservices that previously had to come directly to an institution intended or via phone, but nowthe service is on-line at any time, wherever located so that it can facilitate in handling alltransactions. E-commerce with the company management is very closely related, since ecommerceplay a role here as a means of supporting the marketing to convey information toachieve goals.